Structural Analysis and material selection for biocompatible cantilever beam in soft robotic nanomanipulator - Uddin, Md. Shazib; Khan, Md. Imran; Shafiq, Sadman Bin; Sadik, Shahriar; Rana, Md. Sohel; Bhuiya, Khaled Mohammad Shifullah; Udoy, Sabbir Ahmed; Rafi, Md. Khalid Hasan (BIBECHANA, 2023)
This paper investigates the selection of appropriate materials for cantilever beams in surgical robotic nanomanipulators. Cantilever beams play a crucial role in soft robotic surgery. Biocompatible materials, which have minimal adverse effects on biological systems, are commonly used for these beams. Using SOLIDWORKS software simulation, the study assesses the flexibility of cantilever beams made from different biocompatible materials. The analysis involves varying the applied force (0.001 µN to 0.004 µN), beam length (80 µm, 120 µm, and 160 µm), and beam thickness (0.4 µm, 0.6 µm, and 0.8 µm). Four materials—Alumina, Poly-Ether-Ether-Ketone (PEEK), Polyurethane (PUR), and Ti-6Al-4V—are evaluated. Simulation results highlight Polyurethane (PUR) as a suitable material for cantilever beams in nanomanipulators due to its favorable properties. These findings provide valuable insights for the design and advancement of efficient and reliable robotic nanomanipulators, advancing the field of soft robotic surgery.